Features of the development of private healthcare in Uzbekistan - Kamron Musurmon ugli Abdisayitov; Sherzod Farxodovich Majidov (Science and Education, 2025)
The paper examines the features and role of private medical institutions in Uzbekistan, reveals the features of government support for the development of this sector in the republic.